Urinary Dickkopf-related protein 3 as a novel biomarker for kidney function decline in children with Alport syndrome - Böckhaus, Jan Simon; Tönshoff, Burkhard; Weber, Lutz T.; Pape, Lars; Latta, Kay; Fehrenbach, Henry; Lange-Sperandio, Baerbel; Kettwig, Matthias; König, Sabine; John-Kroegel, Ulrike; Gellermann, Jutta; Galiano, Matthias; et al. (Pediatric nephrology, 2025)
Chronic kidney disease (CKD) seriously affects the well-being and shortens the life expectancy of children and adolescents, but its progression is challenging to predict. Therefore, there is an urgent need for biomarkers that can identify children at risk of faster CKD progression. Alport syndrome (AS) is the most common monogenetic glomerular kidney disease. Urinary Dickkopf-related protein 3 (DKK3) is associated with a decline in estimated glomerular filtration rate (eGFR) in adults and children with advanced CKD. However, its potential for early detection of CKD and its prognostic value in children with AS remain unknown.